THE RELATIONSHIP BETWEEN SOCIAL MEDIA INTENSITY AND SELF-CONFIDENCE IN EARLY ADOLESCENTS - putra, Andi Syah; ndi, Deki Rifa (Universitas Ubudiyah Indonesia, 2021)
The rapid development of social media in people's lives, especially among early teens, has both positive and negative impacts, especially from the psychological aspects of adolescents, especially concerning their self-confidence. Facts on the field show that some students who use social media tend to lack confidence such as having fear when appearing in front of the class, but some students also have courage and high self-confidence. Based on these differences, this study aims to determine the relationship of the intensity of the use of social media to self-confidence in early adolescents. This research method uses a quantitative approach with the type of research is correlation. The population in this study were all adolescents in the MTsN4 Banda Aceh Syiah Kuala District, which amounted to 610 students, while a sample of 86 early adolescents used the rondom sampling technique throughÂ the Slovin formula. Data collection techniques using a questionnaire while data analysis is done by product moment correlation test and t-test. Correlation test results show a value of0.59. While the hypothesis test is known to be greater than t table or 6.700> 1.984 at a significance level of 5%. This means that there is a positive relationship between the intensity of the use of social media with self-confidence in early adolescents. The conclusion is the intensity of the use of social media has a sufficient or moderate relationship with confidence in early adolescents.